Job satisfaction : a reader - Gruneberg, Michael M. (London : Macmillan, 1976)
This book is divided into five parts, aimed at covering the various aspects of job satisfaction which have been described. The first part deals with the nature of job satisfaction, and include papers both favourable to and critical.
Distributed in the U.S. by Halsted Press, New York.
Includes index.
Includes bibliographical references: p. 250-251.
osa 24/01/2019
Loans
Keywords: Job satisfaction